MSME Marketing Strategy Know Fortune Barokah to Increase Product Sales During the Pandemic - Yusup, Ahmad; Ramdani, Deni (CV. Lafadz Jaya, 2022)
The company's external factor is the COVID-19 pandemic which greatly affects the economy and the continuity of the company and MSMEs, one of which is MSME Tahu Fortune Barokah, so MSME Tahu Rejeki Barokah is required to record profits and increase sales volume in these circumstances. The purpose of this research is to find out the marketing mix strategy implemented by the Tahu Rejeki Barokah UMKM during the COVID-19 pandemic. The method in this study uses descriptive qualitative research methods, namely research that utilizes qualitative data and is described descriptively. The data sources used are primary data and secondary data sources. Primary data by interview and documentation from respondents, while secondary data sourced from reports of income and business sales. The results showed that there was a positive influence of the marketing mix strategy applied to the Tahu Rejeki Barokah MSMEs.